Analisis Implementasi Aplikasi BIMA dan Dampaknya terhadap Pengembangan Sumber Daya Manusia di B21 Digital Printing - Al-Kafi, Ahmad Luqmanul Hakim Al-Kafi; Ratih Mukti Azhar (Nirta Learning Centre, 2026)
The rapid development of digitalization in the printing industry requires business actors to adopt technology-based work systems in order to improve operational efficiency and the quality of human resources. This study aims to analyze the implementation of BIMA and its impact on human resource development at B21 Digital Printing. BIMA is a digital system used to record incoming and outgoing goods as well as to manage customer orders in printing operations. This research employs a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving employees directly engaged in the use of BIMA. Data analysis was conducted using the Miles and Huberman model, which includes data collection, data display, and data condensation. The findings indicate that prior to the implementation of BIMA, operational processes were carried out manually, resulting in various problems such as delays in recording, data inaccuracies, and difficulties in monitoring stock and orders. After the implementation of BIMA, there was a significant improvement in operational efficiency, recording accuracy, and workflow transparency. Furthermore, the implementation of BIMA had a positive impact on employees’ work behavior, particularly in terms of discipline, accuracy, and responsibility. However, several challenges remain, especially related to employees’ digital competencies, internet network stability, and the absence of formal standard operating procedures. Overall, BIMA plays an important role in supporting operational management and human resource development at B21 Digital Printing. Keywords: Digitalization, Performance, Human Resources